2015
DOI: 10.1111/cote.12179
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced dyeability of poly(ethylene terephthalate)/organoclay nanocomposite filaments

Abstract: This study deals with the generation of poly(ethylene terephthalate)/organoclay nanocomposite filaments by the melt‐spinning method and with the investigation of their morphological and dyeing properties. Different montmorillonite types of clay (Resadiye and Rockwood) were modified using different intercalating agents, and poly(ethylene terephthalate) nanocomposite filaments containing 0.5 and 1 wt% organoclays were prepared. Afterwards, the filaments were dyed with two disperse dyes (Setapers Red P2G and Seta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A good dispersion of layered silicates in PU elastomer nanocomposites has been found to improve mechanical properties, thermal stability, gas barrier properties and flame retardancy, etc. Although several studies have reported on the dyeing of clay or layered‐silicate nanocomposites of polypropylene , polyethylene terephthalate (PET) , polyamide 6 , polylactic acid (PLA) and PU , there is almost no literature reporting on the dyeing of PU/clay in filament form. Therefore, in the current study PU filaments have been modified by the incorporation of nanoclay to increase their dyeability with acid dye, basic dye and reactive dye.…”
Section: Introductionmentioning
confidence: 99%
“…A good dispersion of layered silicates in PU elastomer nanocomposites has been found to improve mechanical properties, thermal stability, gas barrier properties and flame retardancy, etc. Although several studies have reported on the dyeing of clay or layered‐silicate nanocomposites of polypropylene , polyethylene terephthalate (PET) , polyamide 6 , polylactic acid (PLA) and PU , there is almost no literature reporting on the dyeing of PU/clay in filament form. Therefore, in the current study PU filaments have been modified by the incorporation of nanoclay to increase their dyeability with acid dye, basic dye and reactive dye.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of nanoclay can create void spaces in the PET structure. Such spaces are necessary for penetration of disperse dye molecules from the surface into the interior of the fibre, which in turn improve the disperse dye uptake . Higher K / S values are evidenced by a decrease in lightness ( L * value) and the colour coordinates a *, b *, C * and h ° of the dyeings were affected depending on the uptake of vat and/or disperse dyes used.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, Özen et al . prepared PET/clay nanocomposites filaments via melt compounding with the investigation of their morphological and dyeing properties with disperse dyes. They found that the disperse dye uptake were enhanced by the addition of organoclay to PET, however, the colour fastness properties not adversely affected.…”
Section: Introductionmentioning
confidence: 99%
“…CD-PETs are prepared by using varying amounts of sodium salt of dimethyl ester of 5-sulfoisophthalic acid as a comonomer in their structure. Nanoclays is the most used nanomaterial for modification of synthetic fibers such as polypropylene and PET fibers, [12][13][14][15] and almost all of them showed an enhanced dyeability with nonpolar disperse dyes due to variation of crystalline and amorphous regions in the fiber structures. [7,8] The general approach for producing cationic-dyeable PET polymer is to use a third component containing an anionic sulfonate group during polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic nanoparticles and nanolayers have been a suitable additive, with which synthetic polymers were mixed to increasing its dyeability. Nanoclays is the most used nanomaterial for modification of synthetic fibers such as polypropylene and PET fibers, and almost all of them showed an enhanced dyeability with nonpolar disperse dyes due to variation of crystalline and amorphous regions in the fiber structures. The absorption mechanism of disperse dyes y in the amorphous regions of fiber's structure is physically.…”
Section: Introductionmentioning
confidence: 99%